Participation of the German population of Saratov Province in the charitable activities of the local branch of the Russian Red Cross Society (1870s – early XX century) - Slizhevskaya, Maria R. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The article deals with the problem of previously unexplored charitable activities of the Volga Germans within the framework of the functioning of the Saratov branch of the Russian Red Cross Society. Particular attention is paid to the characterisation of the charity of the local German population of the county towns and villages. It is stated that the types and forms of German charitable activity did not differ from those inherent in the rest of the population of the province. The greatest response, however, in the German environment of the Saratov Volga region were the issues of assistance to the starving and victims of various natural disasters and tragedies, as well as to the soldiers of the Russian Empire.